PENGARUH KETERBUKAAN INFORMASI PUBLIK TERHADAP PEMBANGUNAN DESA DI KANTOR DESA PINANG KECAMATAN CENDANA KABUPATEN ENREKANG - Nurhikmah Aryani JR; Muh. Arisal Asad (JIA: Jurnal Ilmiah Administrasi, 2021)
The type of research used in this study is associative type which aims to determine the effect or relationship between two or more variables. The type of research used in this research is descriptive quantitative research. Because this research will describe the facts and explain the state of the object of research based on the facts as they are and try to analyze to give the truth based on the data obtained in the field. The population in this study amounted to 305 people in Pinang village with a sample of 75 people based on the determination of the sample using the Slovin formula. Data collection techniques used observations, questionnaires, literature studies and interviews. The results of the study indicate that there is a significant influence between public information disclosure on the development of Pinang village, Cendana District, Enrekang Regency. The contribution or determination given by the variable of public information disclosure to village development is D = (0.815)2x 100% = 66%. This means that the variable of public information disclosure contributes 66% to the development of Pinang village, while the remaining 44% is influenced by other variables not included in the study.